The numerical solution of the singular two-point boundary value problems by using non-polynomial spline functions - Çağlar, Hatice Nazan; Çağlar, Süleyman Hikmet; Dündar, Durmuş; Akkoyunlu, Canan (My University, 2010)
The non-polynomial spline method is proposed to solve a singular boundary value problems. Some model problems are solved and the numerical results are compared with B-spline approximation and the exact solution. Results obtained by the method indicate the method is simple and effective.
Keywords: Singular point; Singular two-point boundary value problems; Cubic spline